Multidisciplinary teams for the proper management of patients with genitourinary tumors: When topics set scientific societies' agenda. Issue 2 (April 2019) - Magnani, Tiziana; Bracarda, Sergio; D'Angelillo, Rolando M.; Artibani, Walter; Barni, Sandro; Beretta, Giordano; Brausi, Maurizio; Caffo, Orazio; Corvò, Renzo; Gallucci, Michele; Gunelli, Roberta; Mirone, Vincenzo; et al.
Introduction: The multidisciplinary management of oncologic patients is identified as the bottom line element of quality in tumor care. Methods: In 2015, 7 Italian scientific societies representing the specialists involved in the diagnosis and treatment of genitourinary tumors joined efforts in the Italian uro-oncologic multidisciplinary teams (MDTs) project. The aims were to promote the reorganization of genitourinary cancer care, switching to a multidisciplinary approach, reach a consensus on the core elements for the setup of MDTs in genitourinary oncology, and support health policy makers and managers in remodeling of the assistance and care of uro-oncologic patients on a national level. Results: The first activity was the setup of 5 working groups, given the task of exploring selected topics: general principles, organization of MDTs, minimal requirements, economic evaluation, and relations with authorities. The groups participated in the writing of a document that was approved by the scientific societies and published on their web sites. Moreover, a few items summarizing the extensive document were approved in the first MDT Consensus Conference held in Milan in December 2015. Conclusions: The experience of this initial phase led to the opening of the team to other professionals and societies, in line with a correct management of patients with genitourinary tumors, which need a multidisciplinary as well as a multiprofessional approach with emerging techniques and procedures, and with a new project work package on genitourinary paths of care and indicators.